Morfoanatomia, controle físico-químico e atividade anti-inflamatória de Blepharocalyx salicifolius (Kunth) O. Berg. (Myrtaceae) - Alexandre, Ribas (2011)
The implantation of the quality control in the different stages of development and production, since the collection until the end item is of vital importance to guarantee the security and the consumed vegetal product quality. The Blepharocalyx salicifolius (Kunth). the Berg. it is a native plant in Brazil and popularly used as digestive, stabilizer of the arterial pressure, antitussive and in the cases of bronchitis, cystitis and urethritis. In the present work morphoanatomy analysis was carried through, tests chemical-physical, anti-inflammatory activity and hepatic and renal toxicity of B. salicifolius. To evaluation of the anti-inflammatory activity, was used in the method of induction of granulation tissue formation in rats. Moreover, had been determined the serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinina in the blood of the rats proceeding from the test of granuloma. The leaves of this plant possess epidermis unistratified, without trichomes and present numerous mucilage cells and stomata of the anomocytic and anisocítico type. The mesophyll is heterogeneous, symmetrical, with palisade parenchyma and idioblasts with cristaliníferos druses. The vascular bundles are of collateral type and are protected by a parenchymatous bundle sheath. These morphoanatomy characteristics, when analyzed in set, they contribute in the botanical control of quality of leaves of the B. salicifolius as pharmaceutical ingredient. Parameters were established quality control of the extract of leaves of B.salicifolius through pharmacopoeias tests. The results obtained demonstrate the presence of phenolic, terpenes and esteroides compounds. The values of polyphones and flavonoids had shown that 92.67% of the rude extract are constituted of phenolic compounds and that of these, about one third of the sample are constituted by flavonoides. The highest content of flavonoids was presented in the fraction acetate (35.49%). The crude extract and all the fractions had presented antioxidant activity, being that sharpest they had been rude extract (91.34%) and fractions acetate (86.33%) in the 100 concentration of µg/mL. The antioxidant power can be explained by the phenolic substance presence that is capable to inhibit the free radicals. The group of animals treated with nimesulide presented a inhibition of the inflammatory process of 21,4 ± 6.5%, while the group treated with B.salicifolius demonstrated a inhibition of the inflammatory process of 24,7 ± 4.6%, when compared with the negative control propilenoglicol 20% (p <0,05). The hydroethanolic extract of the B. Salicifolius, administered for a saw verbal, it did not present hepatic and renal toxicity in rats when compared with the negative control.